Born This Way? A Qualitative Examination of Public Perceptions of the Causes of Pedophilia and Sexual Offending against Children. Issue 7 (3rd July 2018) - Richards, Kelly
ABSTRACT: Understanding public opinion about the causes of pedophilia and/or child sex offending is vital, as the views of the public influence how governments respond to sexual offenders. However, little research has been undertaken on this topic. This study addresses this gap by examining the causes that members of the public ascribe to pedophilia and/or child sexual abuse using qualitative data from online forums. The etiological accounts that the public gave provide important information for those developing public prevention policies and/or education campaigns about child sexual abuse. Key implications of these etiological explanations are analyzed in this regard.